Total mesorectal excision: technical aspects - Phang, P. Terry (Canadian Medical Association, 2004)
Total mesorectal excision (TME) is a precise dissection of the rectum and all pararectal lymph nodes within an oncologic package: the mesorectal envelope. This article is a brief description of the technical aspects of the dissection, illustrated by cadaver dissection. Here the TME dissection is organized into 6 steps to facilitate learning: (1) left retroperitoneum; (2) superior rectal and inferior mesenteric vessels; (3) upper mesorectum; (4/5) right and left mid-mesorectum; and (6) distal mesorectum and anorectal junction. The relationship of the autonomic nerves, blood vessels and adjacent organ structures are described at each step. The 6 steps are recommended for learning and performing TME dissection in cadavers and patients.